Stimuli-Responsive, Plasmonic Nanogel for Dual Delivery of Curcumin and Photothermal Therapy for Cancer Treatment - Howaili, Fadak; Özliseli, Ezgi; Küçüktürkmen, Berrin; Razavi, Seyyede Mahboubeh; Sadeghizadeh, Majid; Rosenholm, Jessica M. (Frontiers in Chemistry, 2021)
Nanogels (Ng) are crosslinked polymer-based hydrogel nanoparticles considered to be next-generation drug delivery systems due to their superior properties, including high drug loading capacity, low toxicity, and stimuli responsiveness. In this study, dually thermo-pH-responsive plasmonic nanogel (AuNP@Ng) was synthesized by grafting poly (N-isopropyl acrylamide) (PNIPAM) to chitosan (CS) in the presence of a chemical crosslinker to serve as a drug carrier system. The nanogel was further incorporated with gold nanoparticles (AuNP) to provide simultaneous drug delivery and photothermal therapy (PTT). Curcumin's (Cur) low water solubility and low bioavailability are the biggest obstacles to effective use of curcumin for anticancer therapy, and these obstacles can be overcome by utilizing an efficient delivery system. Therefore, curcumin was chosen as a model drug to be loaded into the nanogel for enhancing the anticancer efficiency, and further, its therapeutic efficiency was enhanced by PTT of the formulated AuNP@Ng. Thorough characterization of Ng based on CS and PNIPAM was conducted to confirm successful synthesis. Furthermore, photothermal properties and swelling ratio of fabricated nanoparticles were evaluated. Morphology and size measurements of nanogel were determined by transmission electron microscopy (TEM), scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX). Nanogel was found to have a hydrodynamic size of 167 nm and exhibited sustained release of curcumin up to 72 h with dual thermo-pH responsive drug release behavior, as examined under different temperature and pH conditions. Cytocompatibility of plasmonic nanogel was evaluated on MDA-MB-231 human breast cancer and non-tumorigenic MCF 10A cell lines, and the findings indicated the nanogel formulation to be cytocompatible. Nanoparticle uptake studies showed high internalization of nanoparticles in cancer cells when compared with non-tumorigenic cells and confocal microscopy further demonstrated that AuNP@Ng were internalized into the MDA-MB-231 cancer cells via endosomal route. In vitro cytotoxicity studies revealed dose-dependent and time-dependent drug delivery of curcumin loaded AuNP@Ng/Cur. Furthermore, the developed nanoparticles showed an improved chemotherapy efficacy when irradiated with near-infrared (NIR) laser (808 nm) in vitro. This work revealed that synthesized plasmonic nanogel loaded with curcumin (AuNP@Ng/Cur) can act as stimuli-responsive nanocarriers, having potential for dual therapy i.e., delivery of hydrophobic drug and photothermal therapy.